Histone modification and histone modification-targeted anti-cancer drugs in breast cancer: Fundamentals and beyond - Feng, Jianwei; Meng, Xinyue (Frontiers in Pharmacology, 2022)
Dysregulated epigenetic enzymes together with the resultant abnormal epigenetic modifications (EMs) have been suggested to be closely related to tumor occurrence and progression. Histone modifications (HMs) can assist in keeping stable genome, DNA repair, transcription, as well as chromatin modulation within breast cancer (BC) cells. In addition, HMs represent the reversible, dynamic processes involving the associations of different enzymes with molecular compounds. Abnormal HMs (e.g. histone methylation, histone acetylation) have been identified to be tightly related to BC occurrence and development, even though its underlying mechanisms remain largely unclear. EMs are reversible, as a result, epigenetic enzymes have aroused wide attention as the anti-tumor therapeutic targets. At present, treatments to restore aberrant EMs within BC are in preclinical or clinical trials. In addition, no existing studies have comprehensively analyzed the aberrant HMs within BC, besides, HMs-targeting BC treatments remain to be further investigated. Histone and non-histone protein methylation is becoming the attractive antitumor epigenetic therapeutic target, such methylation-related enzyme inhibitors have been under development at present. Consequently, the present work focuses on summarizing relevant studies on HMs related to BC as well as the possible mechanisms associated with abnormal HMs. Additionally, we also aim to analyze existing therapeutic agents together with those drugs approved and tested through pre-clinical and clinical trials, so as to assess their roles in HMs. Moreover, epi-drugs that targeted HMT inhibitors and HACT inhibitors should be tested in preclinical and clinical studies for the treatment of BC. Epi-drugs that target histone methylation (HMT inhibitors) and histone acetylation (HDAC inhibitors) are now under clinical trials or are approved by the US Food and Drug Administration (FDA). Therefore, the review covers the difficulties in applying HMs-targeting treatments in clinical and proposes feasible approaches for overcoming such difficulties and promoting their use in treating BC cases.